ダイ17ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1976 - 吉田, 菊治; ヨシダ, キクジ; 外間, 実喜; ホカマ, ジッキ; 榎嶋, 邦夫; エノシマ, クニオ; 加藤, 芳夫; カトウ, ヨシオ; YOSHIDA, Kikuji; HOKAMA, Jikki; ENOSHIMA, Kunio; KATO, Yoshio (1980)
P(論文) この報告は,第17次南極地域観測越冬隊定常気象部門で実施した主たる業務と,その観測成果の概要である.定常気象観測としては,3時間ごとの地上気象観測と,1日2回の高層気象観測を実施し,国際気象電報型式でモーソン基地経由,オーストラリア気象局に通報した.このほかオゾン全量観測も実施した.越冬中の天候は,晴天の日が多かったので冷え込みが厳しく,これに関連した各種気象要素の記録値を更新した.その中で気温については,月平均気温が12月を除き累年値よりすべて低かった.また9月1日には-42.5℃を記録,基地開設以来第2位の低温を示した.南極地方における天気予報は,観測地点が少ないうえに天気変化が激しいので,なかなか困難であったが,隊員の日常作業の便と生命の安全のために,気象衛星写真やソ連基地で放送するFAX天気図をもとに,ブリザードの予報には特に注意して情報を発表した. Meteorological observations at Syowa Station for the 17th expedition were made from February 1, 1976 to January 31, 1977. General and characteristic features in the meteorological observations are summarized as follows : 1) Suface observation : 3-hourly observations were made throughout the whole year and all observations were transmitted by telegram to the Commonwealth Bureau of Meteorology in Melbourne via Mawson Station four times a day. 2) Upper air observation : Twice daily (00 Z and 12 Z) Rawinsonde observations were made throughout the year. All observations were transmitted in the same way as the surface observations. Various types of figures and tables are shown in this report relating to annual variation of mean heights and temperatures, monthly average upper air temperatures, monthly average upper wind profile, wind component, velocity and so on at Syowa Station in 1976. 3) Ozone observation : Total ozone observations were made by using Dobson ozone spectrophotometer throughout the year except from April to August. 4) Significant feature of the weather for that year is that, every monthly average temperature of the year was below the normal value of the respective monthly average, except December. A minimum temperature -42.5℃ recorded on September 1 was the second lowest temperature since the observation had begun in Syowa Station. In other words, fine weather causing the lower temperature has dominated the climate for most part of all the year. 5) It is difficult to make a weather forecast in Antarctica due to not only scanty observations but also changeable weather. We made a special effort to forecast for ...